Refractory Myopic Retinal Detachment and Macular Hole Closure with Autologous Neurosensory Retinal Free Flap - Filipe Sousa Neves; Joana Braga; Paula Sepúlveda; Miguel Bilhoto (Case Reports in Ophthalmology, 2019)
The purpose of this case report is to describe a modified technique involving the use of an autologous neurosensory retinal free flap for closure of a macular hole (MH) during retinal detachment (RD) surgery. A 50-year-old female presented with sudden vision loss (light perception only) and a recurrent myopic RD associated with an MH. An autologous neurosensory retinal free flap was obtained and moved toward the MH. Silicone oil was used as an endotamponade and removed after 6 months. Two months after oil removal visual acuity improved to 20/400 and remained stable thereafter; however, the patient developed central retinal atrophy. One year after surgery the MH was closed and the retina attached. This modified technique with the use of an autologous neurosensory retinal flap provides an alternative approach for recurrent MH in RD procedures.